The Art of Observation: A Pedagogical Framework. (December 2015) - Wellbery, Caroline; McAteer, Rebecca A.
Abstract : Observational skills, honed through experience with the literary and visual arts, bring together in a timely manner many of the goals of the medical humanities, providing thematic cohesion through the act of seeing while aiming to advance clinical skills through a unified practice. In an arts observation pedagogy, nature writing serves as an apt model for precise, clinically relevant linguistic noticing because meticulous attention to the natural world involves scientific precision; additionally, a number of visual metaphors employed in medicine are derived from close observation of the natural world. Close reading reinforces observational skills as part of integrative, multidisciplinary clinical practice. Literary precision provides an educational bridge to recognizing the importance of detail in the clinical realm. In weighing multiple perspectives, observation applied to practice helps learners understand the nuances of the role of witness, activating reflection consonant with the viewer's professional identity. The realization that seeing is highly filtered through the observer's values allows the act of observation to come under scrutiny, opening the observer's gaze to disturbance and challenging the values and precepts of the prevailing medical culture. Application of observational skills can, for example, help observers recognize and address noxious effects of the built environment. As learners describe what they see, they also develop the communication skills needed to articulate both problems and possible improvements within their expanding sphere of influence. The ability to craft this speech as public narrative can lead to interventions with positive impacts on physicians, their colleagues, and patients.